FTIR spectroscopy investigation of “Istihalah” during gelatin production - Aboulala, Slimane; Jaswir, Irwandi; Monsur, Hammed Ademola; Mirghani, Mohamed Elwathig Saeed; Reffice, Bahmed (2014)
Fiqh Istihalah is one of the scientific Islamic branches combine between Islamic study and scientific applied study. Istihalah means transformation of one molecule to another molecule(s), and it is a recognized concept in Halal science. Istihalah of Gelatin is among the top debated topic in halal sciences. This study investigated gelatin transformation during processing from raw materials (hide/skin) to the final product by using Fourier Transform Infra-Red (FTIR) spectroscopy. The results showed that functional group of raw materials and gelatins are the same. This suggests that there is no new bonds introduced thruway gelatin production. Hence, it is confirmed that Istihalah does not occur during gelatin manufacturing.